Pengaruh Model Pembelajaran Collaborative Learning Terhadap Keaktifan Belajar Siswa Pendidikan Agama Kristen Kelas VIII SMP Negeri 4 Siborongborong Tahun Pembelajaran 2022/2023 (Jurnal Pendidikan Agama dan Teologi, 2023)
: The aim of this research is to determine the effect of the Collaborative learning model on the active learning of PAK class VIII students at SMP Negeri 4 Siborongborong for the 2022/2023 academic year. The method used in this research is quantitative descriptive inferential. The population is all class VIII students of SMP Negeri 4 Siborongborong for the 2022/2023 academic year, totaling 205 people and a sample of 41 people was determined, which is 20% of the total population. Data was collected using a positive closed questionnaire with 46 items. The results of data analysis show that there is an influence of the Collaborative Learning model on the active learning of PAK class VIII students of SMP Negeri 4 Siborongborong for the 2022/2023 Academic Year: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.572 > rtable(rtabel(a=0,05,n=41)= 0.05,n=41) = 0.308, thus it is known that there is a positive relationship between variable =39)= 2.021, thus there is a significant relationship between variable b) Regression coefficient of determination test (r2) = 32.7%. 3) Test the hypothesis using the F test to obtain Fhitung > Ftabel=(a=0,05,dk pembilang k=22,dk penyebut=n-2=41-2=39) this 18,97 > 1,51. Thus Ha accepted and H0 rejected.